Features of financial integration of the Eurasian Economic Union member states - B. G. Khairov; V. A. Kovalev; R. Kh. Khasanov (Омский научный вестник: Серия "Общество. История. Современность")
This work is devoted to the study of the issue related to the deepening and expansion of integration processes within the framework of the Eurasian Economic Union for sustainable development, constant technological renewal, increasing the competitiveness of the economies of the Eurasian Economic Union member states and increasing the standard of living of their population. The relevance of the topic is due to the high interest of the state authorities of Russia in the development of this interstate association. The authors use content analysis of regulatory acts and open information materials on mutual financial flows of Eurasian Economic Union member states, analysis of discrete institutional alternatives, mathematical modeling, etc. Based on the analysis carried out in the work, a list of proposals for further progressive development of integration processes in the Eurasian Economic Union was formulated. The article was prepared on the basis of the results of studies carried out at the expense of budgetary allocations within the framework of the state task to the Financial University under the Government of the Russian Federation